2017
DOI: 10.1055/s-0043-110145
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of liver resection in benign solid liver tumors in modern times – in which cases should surgery be done?

Abstract: Due to improved diagnostical and therapeutical approaches, benign liver tumors represent a challenge in clinical management. We here report our experience with patients undergoing liver resection for benign liver tumors. 188 One hundred eighty-eight consecutive patients, who underwent surgery for solid benign liver tumors from 1992 - 2014, were analyzed retrospectively. The focus was on diagnostic pathways, indications for surgery, and perioperative and postoperative quality of life (QoL). Of 188 patients, 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…In contrast, in case series using conventional exams, Perrakis et al [12], Mezhir et al [6] and Hau et al [11] indicated surgery due to diagnostic doubt in 16.1, 38.2, and 47.8% of patients, respectively; in the study of Bieze et al [13], a large number of patients (66.1%) combined with MRI-LSC in which liver biopsy with immunohistochemistry was used, this incidence was zero. With the incorporation of these tests with higher diagnostic accuracy, a progressive and noticeable reduction of this type of surgical indication is expected.…”
Section: Discussion/conclusionmentioning
confidence: 95%
See 3 more Smart Citations
“…In contrast, in case series using conventional exams, Perrakis et al [12], Mezhir et al [6] and Hau et al [11] indicated surgery due to diagnostic doubt in 16.1, 38.2, and 47.8% of patients, respectively; in the study of Bieze et al [13], a large number of patients (66.1%) combined with MRI-LSC in which liver biopsy with immunohistochemistry was used, this incidence was zero. With the incorporation of these tests with higher diagnostic accuracy, a progressive and noticeable reduction of this type of surgical indication is expected.…”
Section: Discussion/conclusionmentioning
confidence: 95%
“…In fact, currently, there are no studies with a good level of evidence that can clearly define the best management course for FNH [5,11].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, surgical treatment is currently used for liver cancer patients without surgical contraindications. SR for benign liver tumors is safe and can significantly improve the quality of life, 26 so SR is also preferred for benign liver tumors requiring treatment 27 …”
Section: Discussionmentioning
confidence: 99%